2022
DOI: 10.1039/d2ma00169a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-incorporated cementitious composites: a thorough investigation

Abstract: The use of nanomaterials, particularly carbon-derived ones, has always been a high-tech topic of research in the field of cement and concrete. Graphene and its derivatives are the most popular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 100 publications
1
10
0
Order By: Relevance
“…Recent reports show that adding a small amount of nanocarbon to the C-S-H matrix drastically increases the mechanical performance of cement-based materials [26][27][28]. For instance, adding a small percentage of graphene oxide to a cement-based composite enhances flexural and compressive strength by 50% and 28%, respectively [29]. Multiple authors obtain similar claims reported in the following references [30][31][32][33].…”
Section: Introductionmentioning
confidence: 53%
“…Recent reports show that adding a small amount of nanocarbon to the C-S-H matrix drastically increases the mechanical performance of cement-based materials [26][27][28]. For instance, adding a small percentage of graphene oxide to a cement-based composite enhances flexural and compressive strength by 50% and 28%, respectively [29]. Multiple authors obtain similar claims reported in the following references [30][31][32][33].…”
Section: Introductionmentioning
confidence: 53%
“…The characterization of our cement paste samples (CG0 and CG05) was conducted using 29 Si Magic Angle Spinning Nuclear Magnetic Resonance ( 29 Si MAS-NMR). The samples, crushed and aged for 7 and 28 days, were analyzed using a Bruker Spectrometer model AV400 MHz WB (Bruker, Billerica, MA, USA).…”
Section: Si Magic Angle Spinning Nuclear Magnetic Resonancementioning
confidence: 99%
“…The relaxation time used for all experiments was 5 s, assuming differential error with respect to the usual acquisition parameters. The chemical shifts of 29 Si were calibrated with reference to Tetramethylsilane (TMS), which was set at 0 parts per million (ppm). This is a standard procedure in NMR spectroscopy as TMS is commonly used as an internal standard due to its high symmetry and low reactivity.…”
Section: Si Magic Angle Spinning Nuclear Magnetic Resonancementioning
confidence: 99%
See 2 more Smart Citations